2021
DOI: 10.1167/iovs.62.3.32
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Retinal Pigment Epithelial Damage at Laser Irradiation in the Lower Microsecond Time Regime

Abstract: Purpose New lasers with a continuous wave power exceeding 15 W are currently investigated for retinal therapies, promising highly localized effects at and close to the Retinal Pigment Epithelium (RPE). The goal of this work is to evaluate mechanisms and thresholds for RPE cell damage by means of pulse durations up to 50 µs. Methods A diode laser with a wavelength of 514 nm, a power of 15 W, and adjustable pulse durations between 2 µs and 50 µs was used. Porcine RPE-chor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…However, for longer pulses, up to 20 µs pulse duration, the damage exposure thresholds reported by Seifert et al were significantly higher than those we observed. This is consistent with the theory that for short pulses, particle absorption by single melanosomes dominates, while for longer pulses, the lower bulk absorption by melanosomes plays a major role [40]. In principle, absolute values should always be considered as rough guide values only, as they can vary greatly and the whole concept of a laser system that compensates for differences in melanin concentration across individuals or across species variations argues against the use of an optimum fixed absolute value.…”
Section: Discussionsupporting
confidence: 80%
“…However, for longer pulses, up to 20 µs pulse duration, the damage exposure thresholds reported by Seifert et al were significantly higher than those we observed. This is consistent with the theory that for short pulses, particle absorption by single melanosomes dominates, while for longer pulses, the lower bulk absorption by melanosomes plays a major role [40]. In principle, absolute values should always be considered as rough guide values only, as they can vary greatly and the whole concept of a laser system that compensates for differences in melanin concentration across individuals or across species variations argues against the use of an optimum fixed absolute value.…”
Section: Discussionsupporting
confidence: 80%
“…This makes any other effect irrelevant, which would happen to the cell otherwise. As it has been reported, at pulse durations shorter than 2 µs, MBF is the initial mechanism for cell damage [5] , [42] , [43] . At the point of MBF, neighboring cells experience an increase in temperature [44] .…”
Section: Discussionmentioning
confidence: 64%
“…In this study, we did not examine the laser pulse energy dependence of the FLT by analyzing the spots inside the pattern, nor the FLT change over a wide area around the pattern. Since the current study with FLIO was conducted as a part of the previously reported study [19], the present study had to be limited to such a partial analysis. There are thus some questions left unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…In order to observe the time-dependent change, the second pattern was applied right next to the first pattern with the same procedure 7-11 days after the first irradiation (Figure 1B left). As mentioned above, these irradiations inside the pattern were performed to investigate the energy threshold of RPE cell death at each pulse length, which was recently reported in another report [19]. Thus, it was difficult to examine the FLT inside the pattern in detail, and it should be noted that this report focuses on the strongly-coagulated marker spots and their surroundings.…”
Section: Laser Irradiationmentioning
confidence: 96%
See 1 more Smart Citation